Resection of Cerebellopontine Angle Meningioma via Retrosigmoid Approach Aiming for Hearing Improvement - Shinya, Yuki; Ono, Hideaki; Inoue, Tomohiro; Tamura, Akira (Journal of Neurological Surgery Part B: Skull Base, 2019)
We present a 71-year-old female case of left cerebellopontine angle (CPA) meningioma who presented with progressive hearing loss. The tumor was 35 mm in maximum diameter, obviously compressed the brain stem and cerebellum, and also displaced cranial nerves 7th and 8th anteriorly (Fig. 1). Retrosigmoid approach was chosen to resect the tumor aiming for hearing improvement. We performed dissection of the tumor from cranial nerves 7th and 8th gently and resection of the tumor except for the part adhesive to these cranial nerves (Fig. 2). Postoperative course was good without any new neurological deficit. Postoperative examination also showed improvement of high-frequency hearing of the left side, and auditory brainstem response demonstrated wave 2 to 5, which was not identify on preoperative examination. These procedures enabled safe and effective resection of the tumor and contributed to hearing improvement.The link to the video can be found at: https://youtu.be/hkRSCxtV3bY.
Keywords: cerebellopotine angle meningioma; retrosigmoid approach; hearing improvement